Pressure‐Induced Enhancement of Photoluminescence and Photocurrent in Organic Semiconductor Rubrene - Zhang, Haiwa; Zhang, Guozhao; Cui, Shouxin; Feng, Haocheng; Chen, Lin; Wang, Qinglin; Li, Qian; Li, Yinwei; Liu, Cailong (Advanced optical materials, 2024)
As a typical organic semiconductor material, rubrene plays a prominent role in the field of optoelectronic devices. Here, a notable photoluminescence (PL) and photocurrent enhancement of rubrene by 8‐ and 2.5‐fold is reported under compression, respectively. The shortening of the π−π stacking distance and the twisting of the lateral phenyl are crucial reasons for the decrease in the bandgap, resulting in the enhancement of PL emission and photocurrent. Pressure can effectively suppress the excitons transition from a free exciton state to a self‐trapped exciton state and improve the emission efficiency. The photocurrent is subject to dual regulation by bandgap and resistance. Interestingly, rubrene undergoes an electronic structure transition at about 4.8 GPa, which is responsible for the weakening of PL emission and photocurrent. This work provides a strategy for optimizing the performance of rubrene‐based optoelectronic devices and designing novel optoelectronic materials. The photoelectric properties of rubrene are closely related to its structure. Pressure significantly enhances the photoluminescence and photocurrent of rubrene by shortening the π–π stacking distance and twisting the lateral phenyl. Rubrene undergoes an electronic structure transition at 4.8 GPa, resulting in the weakening of photoluminescence and photocurrent. Pressure can achieve continuous tunability of the photoelectric properties of rubrene.